2018
DOI: 10.1155/2018/8250521
|View full text |Cite
|
Sign up to set email alerts
|

Netrin as a Novel Biomarker and Its Therapeutic Implications in Diabetes Mellitus and Diabetes-Associated Complications

Abstract: Diabetes is a multifactorial metabolic syndrome and is one of the shared long-lasting illnesses globally. It is linked to long-term microvascular and macrovascular complications that contribute to disability, compromised quality of life, and reduction in lifespan, which eventually leads to death. This disease is not only incurring significant economic burden but also adversely affects the patients, caregivers, communities, and the society at large. The interruption of diabetes progress and its complications is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Type II diabetic patients might require insulin in addition to oral hypoglycemic agents, which is consistently augmented the side effects [7]. In addition, population-wide lifestyle modification, along with early diagnosis and cost-effective treatment of DM, is required to save lives and/or prevent devastating diabetesrelated complications [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Type II diabetic patients might require insulin in addition to oral hypoglycemic agents, which is consistently augmented the side effects [7]. In addition, population-wide lifestyle modification, along with early diagnosis and cost-effective treatment of DM, is required to save lives and/or prevent devastating diabetesrelated complications [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 However, these diagnostic tools are associated with reduced sensitivity and/or specificity to detect diabetes in its early stage. 18 To overcome such problems different newer diagnostic methods were developed by targeting endogenous proteins such as Leptin, TNF-alpha, C-reactive protein (CRP), 19 Netrin, 20 Thioredoxin-interacting protein (TXNIP). 3 But, these novel methods have been also associated with increased cost.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Among them, Netrin was studied by various experimental and clinical models. 7,19,24,32,33 The level of Netrin protein in the plasma has been positively correlated with DR. As compared with the normal controls, the level of Netrin was markedly increased in the early phase of DR. As shown in Table 1, different experimental studies revealed that the level of Netrin in the cornea increased substantially at the early phase of DR ( Table 1).…”
Section: Preclinical and Clinical Studies On The Level Of Netrin In Dmentioning
confidence: 99%
“…2 Due to that protein mostly found in nerve endings were used as indicators for changes which occurred in the system. 7 Among them, Netrin has been recently considered as a novel biomarker and therapeutic agent for DR. Netrin-1…”
Section: Association Of Netrin-1 and -4 With Diabetic Retinopathymentioning
confidence: 99%
See 1 more Smart Citation